2017
DOI: 10.1097/gme.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of electro-acupuncture versus gabapentin for sleep disturbances in breast cancer survivors with hot flashes: a randomized trial

Abstract: Objective Sleep disturbance is a major consequence of hot flashes among breast cancer survivors. This study evaluated the effects of electro-acupuncture vs. gabapentin for sleep disturbances among breast cancer survivors experiencing daily hot flashes. Methods We analyzed data from a randomized controlled trial involving 58 breast cancer survivors experiencing bothersome hot flashes at least two times per day. Participants were randomly assigned to receive eight weeks of electro-acupuncture or daily gabapent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…The common acupoints in the treatment of sleep disturbances were presented in Figure 2 . Garland et al ( 79 ) made a randomized controlled trial involving 58 breast cancer survivors experiencing bothersome hot flashes at least two times per day. Participants were randomly assigned to receive 8 weeks of electroacupuncture or daily gabapentin (total dose of 900 mg/d).…”
Section: Measures To Prevent and Improve Postoperative Sleep Disturbamentioning
confidence: 99%
“…The common acupoints in the treatment of sleep disturbances were presented in Figure 2 . Garland et al ( 79 ) made a randomized controlled trial involving 58 breast cancer survivors experiencing bothersome hot flashes at least two times per day. Participants were randomly assigned to receive 8 weeks of electroacupuncture or daily gabapentin (total dose of 900 mg/d).…”
Section: Measures To Prevent and Improve Postoperative Sleep Disturbamentioning
confidence: 99%
“…Some experimental researches suggest that acupuncture may aid mood imbalances 35 and minimize sleep disturbances. 36 Animal studies found that acupuncture can alleviate the depressive-like behaviors in rats by inhibiting the inflammatory mediators in the hippocampus and prefrontal cortex via modulation of NF-κB pathway. 37 Our previous study found that EA could ameliorate behaviors of depressive model rats by restoring hippocampus CA1 synaptic plasticity, which might be mainly mediated by regulating 5-HT receptor levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kupperman index 3 [34,32,35] 157 −0.36 (−1.08 to 0.37)k P = .74 0.01% P = .34 Physical well-being 8 [17,18,27,28,38,31,40,41] 576 0.08 (−0.44 to 0.60) P = .00 86.5% P = .76 Social well-being 3 [17,27,28] 176 0.08 (−0.21 to 0.38) P = .47 0.00% P = .58 Emotional well-being 176 −0.12 (−0.59 to 0.34) P = .11 53.8% P = .61 TNF 2 [26,27] 64 −0.65 (−1.83 to 0.54) P = .03 77.1% P = .28 IL 2 [26,27] estrogen agonist activity may lead to harmful effects. 43 Shah et al 17 evaluated the estrogen level decline caused by decreased cerebral cortex endorphin levels, which causes secondary vasomotor and psychological symptoms, including increased endometrial carcinoma, irritability, hot flashes, vaginal dryness, loss of libido, menstrual disorders, fatigue, and musculoskeletal side effects.…”
Section: Pathology Parametersmentioning
confidence: 99%